2012
DOI: 10.1038/modpathol.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenoma of the salivary gland: clinicopathological and immunohistochemical analysis of 33 tumors

Abstract: Lymphadenomas (LADs) are rare salivary gland tumors. Their clinicopathologic characteristics and etiopathogenesis are poorly understood. We examined 33 LADs in 31 patients (17 women and 14 men) aged 11-79 years (median 65 years). There were 22 sebaceous LADs in 21 patients (9 women and 12 men) and 11 nonsebaceous LADs in 10 patients (8 women and 2 men). Two patients had synchronous double tumors. Twentysix tumors (79%) arose in parotid, three in the neck, and two each in submandibular gland and oral cavity. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 21 publications
7
90
2
Order By: Relevance
“…While non-sebaceous lymphadenomas do have a stronger female predilection, they are overall biologically similar. Only rare cases of malignant transformation are described [28].…”
Section: Categorical Lumpingmentioning
confidence: 99%
“…While non-sebaceous lymphadenomas do have a stronger female predilection, they are overall biologically similar. Only rare cases of malignant transformation are described [28].…”
Section: Categorical Lumpingmentioning
confidence: 99%
“…It also stains the germinative cells of the secretory portion of sebaceous glands [54]. In a recent paper, p63 stained all sebaceous and NSLs, 11 and 7, respectfully [21], while a separate study found that all 16 metastatic renal cell carcinomas were negative for this antibody [55]. In addition, three primary sebaceous carcinomas of the skin in several recent studies also stained with p63 [54,56,57].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…To date, 22 NSLs have been reported [19][20][21][26][27][28]. Patients typically present with a mass that has been present for up to 5 years.…”
Section: Sebaceous and Non-sebaceous Lymphadenomamentioning
confidence: 99%
See 2 more Smart Citations